Análise e desenvolvimento de algoritmos backstepping aplicados ao controle de corrente de conversores conectados à rede - Araujo, Marcelo Back de (2021)
This master thesis presents control strategies applied to converters connected to the grid. Firstly, mathematical models are obtained, allowing a satisfactory representation of the system. Therefore, control strategies are developed in the continuous time domain, developments of the backstepping technique for converters connected to the grid through an L filter and through the LCL filter are demonstrated, in which graphical analyzes and simulation results are presented to demonstrate the effectiveness of the backstepping technique applied to these systems. In addition, the implications of the discretization of the backstepping technique are analyzed, both for the L filter and for the LCL filter, demonstrating that the development of the backstepping algorithm has additional complexities in the discrete time domain, such as the limitation of gains and stability difficulties in systems with a high relative degree. Thus, a control strategy is proposed combining the backstepping algorithm, which has a simple design and stability guaranteed by the Lyapunov theory, and resonant controllers, which can obtain high gain at determined frequencies. Such control strategy is validated with simulation and experimental results, verifying the strategy’s effectiveness for tracking the grid current, a comparison with resonant controllers with active damping is also performed. Based on experimental results, these two strategies have responses that allow compliance with the harmonic limits determined by the IEEE 1547 standard, showing that the proposed control strategy has a lower harmonic distortion rate than resonant controllers with active damping.